2021
DOI: 10.1111/1365-2664.13856
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding of prey reveals spatial, temporal and diet partitioning of an island ecosystem by four invasive wasps

Abstract: 1. Invasive alien species can cause detrimental changes in native ecosystems, but our understanding of the interactions between multiple exotic species is limited. To

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Unfortunately, we could not compare our species results with those in the study by Schmack et al (2021), as the authors do not provide a list of individual prey species found in the diet of P. chinensis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Unfortunately, we could not compare our species results with those in the study by Schmack et al (2021), as the authors do not provide a list of individual prey species found in the diet of P. chinensis.…”
Section: Discussionmentioning
confidence: 85%
“…On Great Mercury Island, an offshore island in the north of the country, Lepidoptera was the most common order preyed upon by P. chinensis, followed by Hemiptera (fig. 3 in Schmack et al 2021). Thus, while P. chinensis is commonly regarded as a lepidopteran specialist, the fact that cicadas constitute such a regular item preyed upon by these wasps may imply that P. chinensis presents an opportunistic-generalist foraging behaviour described for social wasps (Raveret 2000).…”
Section: Discussionmentioning
confidence: 99%
“…DNA metabarcoding is particularly powerful, when morphological identification of food resources is either very time‐consuming and requiring expert knowledge (such as for pollen) or not possible because hard remains are lacking (such as in faeces). The application of metabarcoding in ecological studies has therefore helped enormously to detect and quantify species interactions for example, of pollinator‐flower interactions (e.g., Casanelles‐Abella et al, 2022) or of predator–prey‐interactions of wasps (Schmack et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular approaches provide another tool for characterizing prey from insect feces. Multiple recent studies have employed metabarcode sequencing of wasp feces to characterize the diets of different wasp species (e.g., [31][32][33]. Metabarcoding has the advantage of identifying prey items over an entire season of wasp activity and from many individuals in the same nest.…”
Section: Introductionmentioning
confidence: 99%